The Utilization Vigna radiata Extract, Coconut Water and Root-Up on The Growth of Bruguiera gymnorrhiza Seedlings - Desi Melianawati; Erma Prihastanti; Sri Haryanti; Endah Dwi Hastuti; Felina Pranata Irawan (Jurnal Biodjati, 2025)
Mangrove forests are declining significantly. Hence, artificial rehabilitation through plant seedlings is necessary. However, failure often occurs due to the low quality of available seedlings. One solution to improve the seedling's quality is the application of growth regulators during mangrove rehabilitation. This study aimed to examine the effect of natural plant growth regulators, namely coconut water and V. radiata extract, as well as the synthetic plant growth regulator root up on the growth of Brugueira  gymnorrhiza seedlings. The research method employed was a Completely Randomized Design (CRD) with a single factor consisting of four treatments and five replications, as follows: P0 = Control, P1 = 100% coconut water, P2 = 10% root up, and P3 = 100% Vigna radiata extract. The observation parameters included plant height, number of leaves, root length, number of roots, stem diameter, and wet weight. Data analysis was conducted with ANOVA and Duncan's Multiple Range Test., natural plant growth regulators (PGRs) considerably improved the growth characteristics of Bruguiera gymnorrhiza seedlings compared to the control and synthetic PGR treatment (Root-Up) (p < 0.05). Among the treatments, Vigna radiata extract had the most impact, with the maximum plant height (51.2 cm), stem diameter (15.264 mm), number of roots (10.6), and fresh weight (33.8 g). Furthermore, the application of coconut water resulted in a considerable rise in the number of leaves, reaching an average of 5.8, as well as increased root elongation with an average length of 10.188 cm. In contrast, using root up at a 10% concentration resulted in no statistically significant improvement in any of the evaluated metrics.